Ultra Structural and Analytical Studies of Biodiesel Producing Microalgae (Chlorella vulgaris and Senedesmis sp.) Collected from Tamil Nadu, India - Kumar, S. Elumalai*, R. Sakthivel; S. Ganesh (Current Botany, 2011)
Microalgae are an economical choice for biofuel production, because of its availability and low cost. Our studies prove that biodiesel can be produced from Freshwater (Temple tanks, Forest lagoons, Inland lakes, Rock ponds) microalgae (Chlorella vulgaris, Senedesmis sp). The Nile Red fluorescence method described in our present study provides a rapid, easily manipulated and reliable method for in vivo quantification of neutral lipids in various microalgal taxa, particularly those belonging to the Chlorophyceae, that were previously found difficult to stain with Nile Red method. The optimum drying period of microalgae biomass is determined to be 120 min. The percentage of lipid content during n-Hexane soaking period (Chlorella vulgaris) is 49% during 210min. Extraction of lipid fragments through solvent extraction method from biomass and the fractions were analysed for biodiesel under FT-IR and GC-MS.